Temporal trends in correlates of HIV testing uptake in South Africa: evaluation and population-level impacts of socio-economic factors and information sources - Wand, Handan; Reddy, Tarylee (Journal of public health, 2022)
Aim The primary objective of this study was to investigate temporal changes in HIV testing rates and quantify the degree to which these trends can be attributed to certain socio-economic characteristics, as well as exposure to information sources. Subjects and methods Data from a nationally representative sample of 30,020 sexually active black Africans who participated in the first, second, third and fourth South African National HIV, Behaviour and Health Surveys conducted in 2002, 2005, 2008 and 2012, respectively. Multivariable logistic regression models and population-attributable risks were calculated for the socio-economic characteristics and the information sources. Results The socio-economic characteristics of the survey participants remained stable over time, while HIV testing rates increased substantially from 20% in 2002 to 70% in 2012. However, there was little improvement in condom use rates. Combined impact of education, employment and geographical locations were associated with increased levels of HIV testing rates. Most of the survey participants (> 80%) were exposed to several mass-media and interpersonal information sources. The combined impact of mass-media tools on HIV testing rates ranged between 48 and 60%, while 40–50% of the HIV tests were collectively attributed to the interpersonal information sources. Conclusion We observed significant temporal changes in population-level impacts of several key socio-economic characteristics and information sources on HIV testing rates. Widespread nationwide HIV awareness efforts led to significant increases in access to testing facilities and substantial increases in HIV testing rates over time. However, this increase was not mirrored in condom use behaviour.